How to protect the world from ultra-targeted biological weapons. (1st November 2020) - Lentzos, Filippa
ABSTRACT: As genomic technologies develop and converge with AI, machine learning, automation, affective computing, and robotics, an ever more refined record of our biometrics, emotions, and behaviors (https://www.npr.org/sections/13.7/2018/02/28/589477976/biometric-data-and-the-rise-of-digital-dictatorship) will be captured and analyzed. These game-changing developments will deeply impact how we view health and treat disease, how long we live, and how we consider our place on the biological continuum. They will also radically transform the dual-use nature of biological research, medicine, and health care and create the possibility of novel biological weapons that target particular groups of people and even individuals. Managing the fast and broad technological advances now under way will require new governance structures that draw on individuals and groups with cross-sectoral expertise – from business and academia to politics and defense.